2020
DOI: 10.21203/rs.3.rs-25903/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modulation of OSCP mitigates mitochondrial and synaptic deficits in a mouse model of Alzheimer’s pathology

Abstract: Background Oligomycin-sensitivity conferring protein (OSCP) is a critical subunit of mitochondrial F1Fo ATP synthase. OSCP dysfunction has been observed in Alzheimer’s disease (AD) brains and a mouse model with AD-like brain amyloidosis (5xFAD mice). However, whether OSCP dysfunction constitutes a key mitochondrial defect contributing to synaptic injury in AD-related conditions has not been comprehensively investigated. Methods Here, we used a 5xFAD mouse model with OSCP overexpression in neurons (Thy-1 OSCP/5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…As mentioned in this review, several studies have demonstrated the presence of mitochondrial dysfunction in the brains of AD patients [76,[276][277][278] and that this could be associated with the impairment of synaptic transmission and cognitive decline present during this disease [279,280]. Furthermore, as was described before, abnormal mitochondrial dynamics, bioenergetics impairment, and oxidative damage are observed in AD [20,93,102].…”
Section: Adsupporting
confidence: 52%
“…As mentioned in this review, several studies have demonstrated the presence of mitochondrial dysfunction in the brains of AD patients [76,[276][277][278] and that this could be associated with the impairment of synaptic transmission and cognitive decline present during this disease [279,280]. Furthermore, as was described before, abnormal mitochondrial dynamics, bioenergetics impairment, and oxidative damage are observed in AD [20,93,102].…”
Section: Adsupporting
confidence: 52%